Organisational climate and its effect on job engagement: exploring the mediating effect of employees level of job satisfaction - Koch, Timothy C (Organisational Psychology, 2014)
This study examined two under-researched organisational climate facets, integration and family-focused supervisor support, as predictors of employees' job engagement. It further set out to explore the extent to which job satisfaction mediated these relationships. Results were based on self-reported survey data from 226 South African employees in the publishing, distribution and advertising industries. Standard multiple regression analysis showed that climates of both integration and family-focused supervisor support were significant predictors of job engagement. Baron and Kenny's four-step approach to mediation revealed that job satisfaction fully meditated the relationships between each of the organisational climate facets and job engagement. Implications for organisational climate research and managers are discussed.